Assessing Writing Proficiency in Bilingual Vocational High School Students: A Case Study at SMKN 1 Tapak Tuan Grade X - Yulita Halim (Indo Publishing, 2026)
This study investigates the writing proficiency of bilingual students in Grade X at SMKN 1 Tapak Tuan, a vocational high school implementing a bilingual instructional model. The research aims to assess students’ overall writing performance and identify the most frequent linguistic issues that influence their proficiency. Using a mixed-method design, data were collected through a writing test, analytic scoring rubric, interviews, and classroom observations. The students’ written texts were evaluated across five components: content, organization, vocabulary, language use, and mechanics. In addition, linguistic errors were categorized using the Error Analysis framework consisting of omission, addition, misformation, and misordering. The findings indicate that most students are positioned at the fair proficiency level, with significant challenges in grammar accuracy, vocabulary range, and organization. Misformation and omission emerged as the most dominant error types, suggesting strong L1 interference and limited exposure to English writing conventions. Qualitative data reveal that students’ difficulties are influenced by low confidence, limited academic vocabulary, and inconsistent bilingual support. The study highlights the need for more explicit writing instruction, targeted feedback, and increased English input within vocational bilingual contexts. Implications for teaching practices and curriculum refinement are also discussed.